Spór o „Solidarność”. Przypadek Liberalno-Demokratycznej Partii „Niepodległość” - Grabowiec, Piotr; Golińczak, Marek (Wydawnictwo Adam Marszałek)
When we research the operation of Worker's Union „Solidarity” (NSZZ „Solidarność”) from the 1980s, interesting is the analysis of the opinions about it held by the people who made up the anti-communist opposition in Poland. Every observer of Polish public debate will surely notice that all the former members of the opposition, as well as people not connected to it, invoke the heritage of „S”. As we know, part of the communities which created various anticommunist organizations or societies, focused around the emerging Union. The best proof of that is the Worker's Defence Committee (KOR), which was created in 1976 and which announced the termination of its operations in 1980. An imprecise observation of the operations of various groups might give the misleading impression that all fully identified with the Union. But when we start a more in-depth research into the operations, publications and statements of various activists, it appears that the matter is far from obvious. A significant reason for highlighting the differences in assessments was the imposition of martial law in December 1981 and the delegalization of „Solidarity”. The dichotomy of worldviews, which is described by antonyms compromise - intransigence, inaction - action, has been characteristic of the discussions in opposition circles in the 1980s.
Keywords: communism; anti-communist opposition; „Solidarity”; civil society